The Microsoft Repository - Bernstein, Phil; Harry, Brian; Sanders, Paul; Shutt, David; Zander, Jason (VLDB 1997, 1997)
The Microsoft Repository is an object-oriented repository that ships as a component of Visual Basic (Version 5.0). It includes a set of ActiveX interfaces that a developer can use to define information models, and a repository engine that is the underlying storage mechanism for these information models. The repository engine sits on top of a SQL database system. The repository is designed to meet the persistent storage needs of software tools. Its two main technical goals are: * compatibility with Microsoft’s existing ActiveX object architecture consisting of the Component Object Model (COM) and Automation and * extensibility by customers and independent software vendors who need to tailor the repository by adding functionality to objects stored by the repository engine and extending information models provided by Microsoft and others. This paper explains how the Repository attains these goals by providing an object-oriented database (OODB) architecture based on Microsoft’s binary object model COM) and type system of Visual Basic (Automation).